Impact Of Stock Repurchase Announcement On Indonesia Stock Market Reaction 2015-2019 - Mandra Lazuardi Kitri; Cristian Eliezer Manurung (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2020)
The negative global sentiment, Corona Virus Disease 2019 (COVID-19) caused several listed companies in Indonesia to conduct a stock repurchase in the hope of maintaining and increasing the company's stock price. The research objective is to analyze the effect of stock repurchase announcements on market reactions that are reflected in abnormal return and trading volume activity in 2015-2019 as a guide for companies to make decisions in the present and the future regarding the same issue. This research uses a sample of 64 companies listed on the Indonesia Stock Exchange (IDX) during the observation period. This study uses the event study method with the significance of the hypothesis test of 0.05. The results showed that there is no significant difference between before and after stock repurchase announcements for both variables. This is caused by the presence of negative sentiment throughout the observation period such as the Brexit tragedy, elections in the US won by Donald Trump, and the issue of the trade war by the US-China, this makes the market does not yet have full trust in the Indonesian capital market. Based on the results of the study, it can be concluded that the stock repurchase announcement did not have a significant effect on the market reaction.